Physical and psychological indicators for canoeing athlete selection - Nurkholis; Mintarto, E.; Hariyanto, A. (Journal of Advances in Social Science and Humanities, 2019)
The athlete selection is very important for the success of the team in the event. The study aim is to establish the dominant variable for canoeing athlete selection based on physical and psychological approach. The type of research is development research. This research was conducted at the national training center canoeing athletes in Jatiluhur, West Java, Indonesia. The results showed that there are two predominant indicators of physical and psychological factors in the selection of canoeing athletes. First, Physical includes of height, sitting height, arm span, stretch height, arm length, back muscle, shoulder, and arm muscle strength, abdominal and arm muscular endurance, explosive power, balance, aerobic and anaerobic capacity. Second, Psychological Skills includes: self-confidence, concentration, motivation, mental readiness, team emphasis, and control anxiety. It can be concluded that the selection of canoeing athletes can be done by measuring the physical and psychological indicators, but not all of the physical and psychological indicators can be used as the instruments in the selection of canoeing athlete.